Research on improvement of project implementation for RFID toll in Malaysia / Syed Mohd Izmir Sabri - Syed Mohd Izmir, Sabri (2022)
In line with the Multi Lane Free Flow (MLFF) concept for tolls in Malaysia, the Ministry of Transportation (MOT) and its agency, Malaysian Highway Authority (MHA), wishes to transition the existing toll payment technology in Malaysia from Touch 'n Go (TNG) cards and Smart Tag to RFID Technology Tag and TNG ewallet. MHA's commencement of the MLFF idea was a watershed moment, signaling a strategic change toward information technology industries, paving the way for Malaysia's development as a developed nation. As it began in 2018, the new payment method received some negative feedbacks from the public, including the RFID tag not being detected, payment being deducted twice, barrier gates not opening when the lane is combined with a Smart Tag/RFID lane, and PLUS highway remains unable to accept payment via RFID tag. This research aims to improve the project management implementation of RFID toll payment up to the global standard. The objectives of this research are to analyses existing toll operations to use RFID toll collection systems in Malaysia, determine the issues of existing RFID toll collection in Malaysia and recommend RFID toll system improvement in Malaysia to an internationally accepted standard. It was decided to employ a qualitative research approach, with primary data gathered through interviews with the many parties who are directly involved in the RFID toll payment such as Malaysian Highway Authority, Touch ‘n Go, all toll concessionaires, JPJ and RFID consultant from Taiwan FETC in order to have better understanding with the current toll operations and the root cause of the challenges with RFID toll in Malaysia. The secondary data was gathered from an existing study paper 5 as well as real-life scenarios from successful countries such as Taiwan and among other sources.